DESIGN OF A HIGH CAPACITY DERRICK CRANE CONSIDERING THE EFFECTS INDUCED BY THE APPLICATION AND THE RELEASE OF THE LOAD - Solazzi, Luigi; Zrnic, Nenad (Journal of Applied Engineering Science, 2017)
This paper presents the main results of a research on the design of a very large derrick crane (the main boom length is 80 m and the payload is 60 t) considering the dynamic effects induced by moving load. The research was developed considering the dynamic effects which are the increase of the external actions as a result of the movement of the load itself. The work was developed through a preliminary design using analytical schemes which have been followed by Fem analyses (static and modal) in order to evaluate the dynamic behavior of the crane. Subsequently they have been implemented different moving load patterns in order to study the structure response during the time. The analyses show that the dynamic actions are much higher in the case of sudden load release compared with the situation of simple load application and that the entity is related both to natural frequencies of the structure and to the fundamental ones related to the load application mode. The analyses performed show also the buckling phenomena is the most dangerous for the arm and these phenomena justify the collapse of the arm in similar crane.
Keywords: Lifting equipment; Derrick crane; Finite element methods; Modal analyses; Dynamical behavior; Dynamic load; Dynamics effects; Moving loads